A novel strain-specific neutralizing epitope on glycoprotein H of human cytomegalovirus - Thomas, Marco; Kropff, Barbara; Schneider, Andrea; Winkler, Thomas; Görzer, Irene; Sticht, Heinrich; Britt, William J.; Mach, Michael; Reuter, Nina (Journal of Virology, 2021)
Human cytomegalovirus (HCMV) is a ubiquitous pathogen that causes severe clinical disease in immunosuppressed patients and congenitally infected newborn infants. Viral envelope glycoproteins represent attractive targets for vaccination or passive immunotherapy. To extend the knowledge of mechanisms of virus neutralization, monoclonal antibodies (MAbs) were generated following immunization of mice with HCMV virions. Hybridoma supernatants were screened for in vitro neutralization activity, yielding three potent MAbs, 6E3, 3C11, and 2B10. MAbs 6E3 and 3C11 blocked infection of all viral strains that were tested, while MAb 2B10 neutralized only 50% of the HCMV strains analyzed. Characterization of the MAbs using indirect immunofluorescence analyses demonstrated their reactivity with recombinantly derived gH. While MAbs 6E3 and 3C11 reacted with gH when expressed alone, 2B10 detected gH only when it was coexpressed with gB and gL. Recognition of gH by 3C11 was dependent on the expression of the entire ectodomain of gH, whereas 6E3 required residues 1 to 629 of gH. The strain-specific determinant for neutralization by Mab 2B10 was identified as a single Met!Ile amino acid polymorphism within gH, located within the central part of the protein. The polymorphism is evenly distributed among described HCMV strains. The 2B10 epitope thus represents a novel strain-specific antibody target site on gH of HCMV. The dependence of the reactivity of 2B10 on the simultaneous presence of gB/gH/gL will be of value in the structural definition of this tripartite complex. The 2B10 epitope may also represent a valuable tool for diagnostics to monitor infections/reinfections with different HCMV strains during pregnancy or after transplantation. IMPORTANCE HCMV infections are life threatening to people with compromised or immature immune systems. Understanding the antiviral antibody repertoire induced during HCMV infection is a necessary prerequisite to define protective antibody responses. Here, we report three novel anti-gH MAbs that potently neutralized HCMV infectivity. One of these MAbs (2B10) targets a novel strain-specific conformational epitope on gH that only becomes accessible upon coexpression of the minimal fusion machinery gB/gH/gL. Strain specificity is dependent on a single amino acid polymorphism within gH. Our data highlight the importance of strain-specific neutralizing antibody responses against HCMV. The 2B10 epitope may also represent a valuable tool for diagnostics to monitor infections/reinfections with different HCMV strains during pregnancy or after transplantation. In addition, the dependence of the reactivity of 2B10 on the simultaneous presence of gB/gH/gL will be of value in the structural definition of this tripartite complex.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Glycoprotein H; Herpesviruses; Human cytomegalovirus; Neutralizing antibodies